Lipotoxicity mediates Glutaredoxin 5 deficiency and impaired Fe-S cluster synthesis in β-cells promoting ferroptosis - Römer, Axel; Justus Liebig University Giessen (My University, 2025)
Glutaredoxin 5 (Glrx5), a key carrier protein for iron-sulfur clusters within the mitochondrial iron-sulfur cluster assembly machinery, may represent a relevant mechanism contributing to the development of type 2 diabetes under lipotoxic stress. Impairments in iron-sulfur clusters can lead to mitochondrial dysfunction and dysregulated iron homeostasis, triggering iron-dependent peroxidation of cell membranes and β-cell decay (ferroptosis). Such disruptions in mitochondrial integrity can have profound consequences on cellular metabolism and survival. Treatment of wild type and Glrx5-modified MIN6 cells with oleic acid revealed a detrimental shift in NADH dependent redox potential, as assessed by MTT analysis. Protein analysis showed diminished levels of intracellular insulin and Glrx5, along with decreased Ins2 gene expression, while Glrx5 gene expression remained unchanged, suggesting post-transcriptional regulatory mechanisms. Among iron-sulfur proteins upon oleic acid treatment, cytosolic aconitase activity was attenuated, accompanied by lower protein levels of PolD1 and GPAT. In contrast, mitochondrial aconitase activity, respiratory chain complexes II, III, and IV, and immunoblot signals of cytosolic aconitase, mitochondrial aconitase, UQCRC2, UQCRFS1, COX-2, and COX-6 A/B remained unaffected, highlighting a selective vulnerability to lipotoxic stress. Additional proteins unrelated to Glrx5, such as p-ERK1/2, PDX1, NDUFB8 and the iron-storage protein ferritin light chain, were negatively impacted by oleic acid treatment, further emphasizing the complex regulatory network involved in iron metabolism. Functional impairments in mitochondrial respiration and ATP levels were detected. All observed effects were not reversed by Glrx5 transfection, indicating that Glrx5 may not be the major factor for lipotoxic pathophysiology. Similarly, oleic acid treatment of human EndoC-βH3 cells mirrored the ATP level response seen in MIN6 cells, reinforcing the potential relevance of these findings for human β-cell physiology. The attenuation of cytosolic aconitase activity, despite unchanged immunoblot signals, could be caused by a loss of the iron-sulfur cluster. This could disrupt iron regulation, as indicated by ferritin levels. The findings highlight the response of selected iron-sulfur proteins to lipotoxic stress, suggesting their potential role in the pathogenesis of type 2 diabetes. Further experimental exploration of lipotoxicity-related mechanisms and their impact on mitochondrial and cytosolic iron-sulfur proteins is essential for understanding the development and potential therapeutic targets of type 2 diabetes.
tosis
Keywords: Diabetes; Diabetes mellitus type 2; iron sulfur cluster; lipotoxicity; beta cell; cell culture; Glutaredoxin 5; oleic acid; ddc:610